Challenges and Advances in Gender Equity: Analysis of Policies, Labor Practices, and Social Movements - Kiara Geoconda Peralta-Jaramillo (Social Sciences)
Gender equity is one of the most complex contemporary challenges, encompassing political, economic, labor, and cultural dimensions. This study aims to analyze the impact of public policies, labor practices, and social movements in promoting gender equity across various socio-political contexts. To answer the central question of how these elements influence a reduction in gender inequalities, a Systematic Literature Review (SLR) was conducted, complemented by a Bibliometric Analysis, following PRISMA protocol guidelines. The bibliographic search, carried out in the Scopus database, covered the period from 2015 to 2025 and identified 26 relevant studies that met the predefined inclusion criteria. The results reveal that, despite progress in formulating policies aimed at combating gender-based violence and promoting equality, the implementation of these measures is hindered by a lack of inter-institutional coordination and the persistence of deeply rooted cultural norms. Likewise, structural inequalities in the labor sphere are evident, such as the gender wage gap and barriers to professional advancement. On the other hand, social movements have emerged as key actors—including governmental institutions, civil society organizations, and healthcare providers—in highlighting and transforming these disparities by driving changes in political agendas and increasing women’s representation in decision-making positions. In summary, this study underscores the need to adopt intersectional and comprehensive approaches to achieve effective and sustainable gender equity, while comparing the influence of policies across different global regions.